Crystal structure of human adenovirus at 3.5 Å resolution - Reddy, Vijay S. (2010)
Rational development of adenovirus vectors for therapeutic gene transfer is hampered by the lack of accurate structural information. Here we report the X-ray structure at 3.5 Å resolution of the 150 megadalton adenovirus capsid containing nearly 1 million amino acids. We describe interactions between the major capsid protein (hexon) and several accessory molecules that stabilize the capsid. The virus structure also reveals an altered association between the penton base and the trimeric fiber protein, perhaps reflecting an early event in cell entry. The high-resolution structure provides a significant advance towards understanding the assembly and cell entry mechanisms of a large dsDNA virus and provides new opportunities for improving adenovirus-mediated gene transfer.